A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener - Bukejs, Andris; Alekseev, Vitalii I.; Cooper, David M.l.; King, Gavin A.; Mckellar, Ryan C. (Zootaxa, 2019)
Based on a well-preserved specimen from Eocene Baltic amber, the second fossil species belonging to the genus Pycnomerus Erichson (Coleoptera: Zopheridae: Zopherinae), P. agtsteinicus Bukejs, Alekseev & McKellar sp. nov. is described and illustrated using synchrotron X-ray micro-CT observations. The new species adds to the sparse fossil record of Pycnomerus, which consists of the Baltic amber discoveries, and only four subfossil records in sediments that are less than one million years old. As part of this work, the new replacement name Pycnomerus lordi Bukejs, Alekseev & McKellar nom. nov. is also established for the extant species Pycnomerus sulcicollis LeConte, 1863 [non Pycnomerus sulcicollis (Germar, 1824)].